An analytical model for 2D seismic tunnel-aboveground structure interaction with considering the influence of tunnel longitudinal shear deformation. Issue 4 (November 2022) - Jin, Liguo; Du, Liting; Xie, Junju; Li, Xiaojun
The influence of tunnel longitudinal shear deformation on the response of its adjacent ground building is investigated based on a 2D analytical model considering a flexible circular tunnel and a shear wall standing on a semi-circular rigid foundation under SH-waves excitation. Soil-tunnel relative stiffness is introduced, and a closed-form analytical solution is presented for the system response. Tunnel stiffness significantly affects the foundation impedance function of the building. Rayleigh scattering frequency can accurately predict the position of the fluctuation peaks of the foundation impedance function. At locations where the tunnel–building interaction is strong, the tunnel cannot be considered as rigid even if the tunnel relative stiffness to the soil reaches 100. At locations where constructive and destructive wave interference occurs, the building relative response increases or decreases accordingly. Considering the influence of tunnel relative stiffness, the amplitude of the building relative response can be amplified by 27.0% or reduced by approximately 28.0%, respectively. This analytical model is also used to qualitatively predict the amplitude of the relative response transfer function of the Hollywood Storage Building under the influence of the tunnel longitudinal shear deformation, and its accuracy is verified.